Pediatric Acute Promyelocytic Leukemia: Epidemiology, Molecular Features, and Importance of GST-Theta 1 in Chemotherapy Response and Outcome - Andrade, Francianne G.; Feliciano, Suellen V. M.; Sardou-Cezar, Ingrid; Brisson, Gisele D.; Santos-Bueno, Filipe V. dos; Vianna, Danielle T.; Marques, Luísa V. C.; Terra-Granado, Eugênia; Zalcberg, Ilana; Santos, Marceli de O.; Costa, Juliana T.; Noronha, Elda P.; et al. (Frontiers in Oncology, 2021)
Previous studies have suggested a variation in the incidence of acute promyelocytic leukemia (APL) among the geographic regions with relatively higher percentages in the Latin American population. We aimed to explore the population burden of pediatric APL, gathering information from the population-based cancer registry (PBCR) and the diagnosis of APL obtained through incident cases from a hospital-based cohort. The homozygous deletion in glutathione S-transferases (GSTs) leads to a loss of enzyme detoxification activity, possibly affecting the treatment response. Mutations in the RAS pathway genes are also considered to be a key component of the disease both in the pathogenesis and in the outcomes. We have assessed mutations in a RAS–MAP kinase pathway (FLT3, PTPN11, and K-/NRAS) and GST variant predisposition risk in the outcome. Out of the 805 children and adolescents with acute myeloid leukemia (AML) who are registered in the PBCR, 35 (4.3%) were APL cases. The age-adjusted incidence rate (AAIR) was 0.03 per 100,000 person-years. One-hundred and sixty-three patients with APL were studied out of 931 AML cases (17.5%) from a hospital-based cohort. Mutations in FLT3, KRAS, and NRAS accounted for 52.1% of the cases. Patients with APL presented a 5-year probability of the overall survival (OS) of 67.3 ± 5.8%. A GST-theta 1 (GSTT1) null genotype conferred adverse prognosis, with an estimated hazard ratio of 2.8, 95% confidence interval (CI) 1.2–6.9. We speculate that the GSTT1 polymorphism is associated with therapeutics and would allow better OS of patients with APL with a GSTT1 null genotype.